Community-Based Human Resource Management in Quality Early Childhood Education - Abubakar, Abubakar; Juhadira, Juhadira; Puspitasari, Yulinda; Nasir, Nasir; Muliyani, Muliyani; Rasid, Rasid; Bagea, Ishak (Universitas Ahmad Dahlan, 2024)
This research investigates community-based human resource management (HRM) in the context of Quality Early Childhood Education (ECE). The primary objective is to analyze the effectiveness of an HRM approach involving active community participation in enhancing the quality of Early Childhood Education services. This study examines community-based HRM in early childhood education through a literature review. The findings reveal that a community-based HRM approach can positively contribute to improving ECE quality. Active community involvement in decision-making processes, collaborative training, and ongoing mentorship for ECE teachers and educators create a more effective and inclusive learning environment. The implications of this research underscore the importance of community involvement in the development and strengthening of quality ECE. Additionally, the study guides policymakers and education practitioners to integrate community-based elements into ECE HRM strategies.